A nucleating agent for improving the wear resistance of PE materials and its preparation method and application

The nucleating agent produced by the composite of talc powder and fluorenyl ring amide solves the problem of improving the crystallization and wear resistance of polyethylene materials in the prior art, and achieves efficient crystallization and significant wear resistance of polyethylene materials.

CN118930969BActive Publication Date: 2025-04-18ANHUI RUIYUAN PIPELINE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411184230.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-04-18
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

In the prior art, a single nucleating agent has relatively limited improvements in the crystallization properties and crystallization forms of polyethylene materials, and has relatively limited improvements in the wear resistance of polyethylene materials.

Method used

A nucleating agent is obtained by combining talc powder with fluorene ring amide. The fluorene ring amide has an amide-based β crystal structure, which can improve the crystallinity of the polyethylene material and promote its transformation from an α crystal form to a β crystal form with smaller grain size, thereby improving wear resistance.

Benefits of technology

This nucleating agent effectively improves the crystallization rate and crystallinity of polyethylene materials, and at the same time significantly enhances its wear resistance, making it widely used in the nucleating agent field of PE materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118930969B_ABST
    Figure CN118930969B_ABST
Patent Text Reader

Abstract

The present invention discloses a nucleating agent for improving the wear resistance of PE materials, a preparation method and an application thereof, wherein the nucleating agent for improving the wear resistance of PE materials is prepared by compounding talcum powder and fluorene cyclic amide; the fluorene cyclic amide has a structure shown in the following formula A. The nucleating agent for improving the wear resistance of PE materials provided by the present invention is prepared by compounding talcum powder and fluorene cyclic amide, and the combination of an inorganic nucleating agent and an organic nucleating agent having a fluorene ring and a pyridine structure can effectively improve the crystallization morphology of the PE material, thereby improving the crystallization rate and crystallinity of the PE material, and at the same time significantly enhancing the wear resistance of the PE material, so that the nucleating agent can be widely used in the field of nucleating agents for PE materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of organic polymer auxiliary compounds, and in particular to a nucleating agent for improving the wear resistance of PE materials, and a preparation method and application thereof. Background Art

[0002] As one of the five major general-purpose plastics, polyethylene (PE) has good chemical stability and a wide variety of varieties. It is widely used in food packaging, cable insulation, engineering plastics, daily necessities and other fields. Polyethylene is a polymer formed by the polymerization of ethylene monomers. It is a crystalline thermoplastic resin and one of the five major synthetic resins. It is the variety with the largest production capacity and the largest import volume among my country's synthetic resins. Polyethylene has a wide range of uses, and the microstructure is the key to determining the use of polyethylene.

[0003] Polyethylene is a semi-crystalline polymer material. The morphology and content of the crystalline and amorphous regions are critical to the performance of polyethylene. Usually, the cooling process of polymer processing is accompanied by a crystallization process, which is divided into two stages: nucleation and growth. The nucleation process refers to the molecular chain overcoming the critical nucleation work to form a crystal nucleus, and the growth process refers to the molecular chain growing on the formed crystal nucleus.

[0004] The use of nucleating agents is an important way to regulate the properties of semi-crystalline polymers. Adding nucleating agents to semi-crystalline polymers can change their crystallization behavior, increase the crystallization temperature and crystallization rate, and reduce the crystal size, thereby increasing the transparency of the material, improving the mechanical properties and rigidity of the material, shortening the molding cycle, and improving warpage deformation.

[0005] Nucleating agents can be divided into organic small molecule nucleating agents, inorganic nucleating agents and polymer nucleating agents according to their structures. Organic small molecule nucleating agents include carboxylic acids and their salts, sorbitol, stearates, etc., which are the most widely used type of nucleating agents, but they are often expensive. Inorganic nucleating agents include TiO2, SiO2, CaCO3, montmorillonite, talc, etc. Compared with organic small molecule nucleating agents, inorganic nanoparticle nucleating agents are cheap and can also enhance the matrix, but their dispersion in the matrix is ​​poor, which affects the nucleation effect. Polymer nucleating agents refer to certain high melting point polymers that have good compatibility with the polymer body, but compared with the first two types of nucleating agents, their manufacturing technology is immature and they are less used.

[0006] Organic nucleating agents can overcome the disadvantage of poor compatibility of inorganic nucleating agents with semi-crystalline plastic matrices. Therefore, organic nucleating agents are usually used in the molding of semi-crystalline plastics.

[0007] However, the single nucleating agent in the prior art has limited effect on improving the crystallization performance and crystal morphology of polyethylene materials, and the organic nucleating agent in the prior art has limited effect on improving the wear resistance of polyethylene materials.

[0008] Therefore, there is an urgent need for a nucleating agent that can effectively increase the crystallization rate and crystallinity of PE materials and significantly improve the wear resistance. Summary of the invention

[0009] Purpose of the invention: In view of the defects of the prior art, the purpose of the present invention is to provide a nucleating agent and its preparation method and application which can effectively improve the crystallization rate and crystallinity of PE materials and significantly enhance the wear resistance of PE materials.

[0010] Technical solution:

[0011] A nucleating agent for improving the wear resistance of PE materials, prepared by compounding talc powder and fluorene cyclic amide;

[0012] The fluorene cyclic amide has a structure shown in the following formula A:

[0013]

[0014] The fluorene cyclic amide in the present invention is an amide-type β-crystal nucleating agent, which can not only improve the crystallinity of the PE material, but also promote its transformation from the α-crystal to the β-crystal with a smaller grain size, thereby effectively improving the wear resistance of the PE material.

[0015] Further, the fluorene ring amide is prepared by the following steps:

[0016] (1) subjecting 6-methyl-2-pyridinecarboxylic acid to an acylation reaction to obtain a pyridine intermediate;

[0017] (2) The pyridine intermediate is reacted with 2,7-diaminofluorene to obtain the fluorene cyclic amide.

[0018] Furthermore, the specific method of step (1) is: adding 6-methyl-2-pyridinecarboxylic acid, thionyl chloride and a dehydrating agent into a reactor, heating to 70-80° C. and reflux reacting for 24-36 hours, evaporating, washing and drying to obtain the pyridine intermediate.

[0019] In the present invention, the pyridine structure in the fluorene cyclic amide can improve the rigidity-toughness balance of the PE material, which can not only improve the mechanical properties of the PE material, but also improve the wear resistance of the material.

[0020] Furthermore, the dehydrating agent is selected from one of dicyclohexylcarbodiimide, N,N'-diisopropylcarbodiimide or 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide; and the mass ratio of the 6-methyl-2-pyridinecarboxylic acid to thionyl chloride is 1:8-12.

[0021] Furthermore, the specific method of step (2) is: adding pyridine intermediate, 2,7-diaminofluorene, catalyst and organic solvent into a reactor, heating to 60-70°C for 6-8 hours, filtering, washing and drying to obtain the fluorene cyclic amide.

[0022] In the present invention, the fluorene ring structure in the fluorene ring amide has excellent rigidity in space. On the one hand, it can effectively play the role of crystal nucleus to improve the crystallization rate and crystallinity of PE materials; on the other hand, it can be evenly dispersed in the crystal pores of PE materials to support the stability of the overall structure, thereby significantly enhancing the wear resistance of PE materials.

[0023] Furthermore, the catalyst is selected from one of triethylamine and triphenylphosphine; the organic solvent is selected from one of N,N-dimethylformamide, dichloromethane and tetrahydrofuran; and the mass ratio of the pyridine intermediate to 2,7-diaminofluorene is 1:1.5-2.

[0024] Furthermore, the talcum powder has a particle size of 1000-1500 mesh.

[0025] Furthermore, the mass ratio of the talc powder to the fluorene cyclic amide is 1:6-8.

[0026] The present invention can achieve a synergistic effect by compounding the inorganic nucleating agent talc powder with fluorene cyclic amide, thereby improving the crystallization uniformity and density of the PE material, and further effectively improving the wear resistance of the PE material.

[0027] Any of the above-mentioned methods for preparing a nucleating agent for improving the wear resistance of PE materials comprises the following steps: adding talcum powder and fluorene cyclic amide in proportion in a reactor, heating to 50-60° C. for dehydration and mixing for 30-40 minutes, and vacuum drying to obtain the nucleating agent for improving the wear resistance of PE materials.

[0028] Application of any of the above nucleating agents for improving the wear resistance of PE materials in PE materials.

[0029] Beneficial effects:

[0030] (1) The nucleating agent for improving the wear resistance of PE materials provided by the present invention is prepared by compounding talcum powder and fluorene ring amide. By combining the inorganic nucleating agent with the organic nucleating agent having a fluorene ring and a pyridine structure, the crystal morphology of the PE material can be effectively improved, thereby increasing the crystallization rate and crystallinity of the PE material, and at the same time significantly enhancing the wear resistance of the PE material, so that it can be widely used in the field of nucleating agents for PE materials.

[0031] (2) Among the nucleating agents for improving the wear resistance of PE materials provided by the present invention, fluorene cyclic amide is an amide-type β-crystal nucleating agent, which can not only improve the crystallinity of PE materials, but also promote the transformation from α-crystal to β-crystal with smaller grain size, thereby effectively improving the wear resistance of PE materials.

[0032] (3) In the nucleating agent for improving the wear resistance of PE materials provided by the present invention, the fluorene ring structure in the fluorene ring amide has excellent rigidity in space. On the one hand, it can effectively play the role of a crystal nucleus to improve the crystallization rate and crystallinity of the PE material; on the other hand, it can be evenly dispersed in the crystal pores of the PE material to support the stability of the overall structure, thereby significantly enhancing the wear resistance of the PE material.

[0033] (4) In the nucleating agent for improving the wear resistance of PE materials provided by the present invention, the pyridine structure in the fluorene cyclic amide can improve the rigidity and toughness balance of the PE material, which can not only improve the mechanical properties of the PE material, but also improve the wear resistance of the material.

[0034] (5) In the nucleating agent for improving the wear resistance of PE materials provided by the present invention, the inorganic nucleating agent talc powder is compounded with fluorene cyclic amide, which can play a synergistic role, improve the crystallization uniformity and density of the PE material, and thus effectively improve the wear resistance of the PE material. DETAILED DESCRIPTION

[0035] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0036] The commercially available organic nucleating agent is nucleating agent 3988 purchased from Hubei Chushengwei Chemical Co., Ltd.; the remaining reagents and equipment are conventional reagents and equipment in the technical field.

[0037] Preparation of Fluorene Cyclic Amide

[0038] Fluorene cyclic amide was prepared by the following steps:

[0039] (1) In a reactor, 2 g of 6-methyl-2-pyridinecarboxylic acid, 20 g of thionyl chloride and 0.3 g of dicyclohexylcarbodiimide were added, the temperature was raised to 75° C. and refluxed for 2 hours, and then evaporated, washed and dried to obtain a pyridine intermediate;

[0040] (2) In a reactor, 2 g of a pyridine intermediate, 3 g of 2,7-diaminofluorene, 0.1 g of triethylamine and 100 mL of N,N-dimethylformamide were added, and the mixture was heated to 70° C. for 8 hours, and then filtered, washed and dried to obtain the fluorene cyclic amide;

[0041] Mass spectrum data of fluorene cyclic amide: The product was analyzed by LC-MS, and the m / z of the product was 434.17 (100.0%), 435.19 (31.3%), and 436.19 (4.8%).

[0042] Example 1

[0043] The nucleating agent for improving the wear resistance of PE materials is prepared by the following steps:

[0044] In a reactor, 1 part of 1500-mesh talc and 6 parts of fluorene cyclic amide were added by weight, heated to 60° C. for dehydration and mixing for 30 minutes, and then vacuum dried to obtain the nucleating agent for improving the wear resistance of PE materials.

[0045] Example 2

[0046] The method is basically the same as Example 1, except that the talc powder is changed to 1200 mesh; and the fluorene cyclic amide is changed to 7 parts.

[0047] Example 3

[0048] The method is basically the same as Example 1, except that the talc powder is changed to 100 mesh; and the fluorene cyclic amide is changed to 8 parts.

[0049] Comparative Example 1

[0050] Commercially available organic nucleating agents.

[0051] Comparative Example 2

[0052] The process is basically the same as Example 1, except that the fluorene cyclic amide is replaced by an equal amount of hydroxyaluminum p-tert-butylbenzoate.

[0053] Comparative Example 3

[0054] The method is basically the same as Example 1, except that talc is replaced with an equal amount of fluorene cyclic amide.

[0055] Performance Testing

[0056] The products of Examples 1-3 and Comparative Examples 1-3 were mixed with polyethylene powder at a mass ratio of 1:40, and after being mixed evenly, they were added to a screw extruder for granulation. The temperatures of the first to fifth sections of the extruder screw were set to 200, 210, 210, 210, 210, 190° C., and the screw speed was 150 r / min. The composite material particles were injection molded into strips at 220-230° C., an injection pressure of 10 MPa, and a cooling time of 15 s.

[0057] Crystallization enthalpy detection: German Netzsch differential scanning calorimeter DSC 3500 was used to detect the prepared specimens according to GB / T 19466.3-2004 "Plastic Differential Scanning Calorimetry" standard. The cooling rate was set to 5°C / min, and the crystallization enthalpy value was obtained by integral calculation. The larger the crystallization enthalpy value, the more effective the nucleating agent is, and the crystallization rate and crystallinity of the obtained polylactic acid are greater.

[0058] Thermal deformation temperature test: According to GB / T 1634-1979 "Test method for thermal deformation temperature of plastics under bending load", the thermal deformation temperature of the specimens prepared above was tested.

[0059] Wear resistance test: According to GB / T 3960-2016 plastic sliding friction and wear test method, the volume wear of the above-prepared specimens was tested.

[0060] The test results are shown in the following table:

[0061] Crystallization enthalpy (kJ / kg) Heat deformation temperature(℃) <![CDATA[Volume wear (×10 -4 cm 3 )]]> Example 1 37 108 2.5 Example 2 37 110 2.6 Example 3 38 110 2.5 Comparative Example 1 29 82 4.2 Comparative Example 2 33 102 3.3 Comparative Example 3 34 104 2.9

[0062] According to the comparison of the test results of Examples 1-3 with those of Comparative Example 1, the nucleating agent for improving the wear resistance of PE materials provided by the present invention can effectively improve the crystallization rate and crystallinity of PE materials compared with the nucleating agent in the prior art, and can significantly enhance the wear resistance of PE materials, and can be widely used in the field of nucleating agents for PE materials.

[0063] According to the comparison of the test results of Examples 1-3 and Comparative Example 2, it can be seen that among the nucleating agents for improving the wear resistance of PE materials provided by the present invention, fluorene cyclic amide can further improve the crystallization rate and crystallinity of PE materials, and can enhance the wear resistance of PE materials.

[0064] According to the comparison of the test results of Examples 1-3 with those of Comparative Example 3, the nucleating agent for improving the wear resistance of PE materials provided by the present invention has a certain synergistic effect by combining the inorganic nucleating agent talc powder and the organic nucleating agent fluorene cyclic amide, which can further improve the crystallization rate and crystallinity of the PE material and further improve its wear resistance.

[0065] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A nucleating agent for improving the wear resistance of PE materials, characterized in that: It is prepared by compounding talc powder with fluorene cyclic amide; The fluorene cyclic amide has a structure as shown in the following formula A: ; The talcum powder particle size is 1000-1500 mesh; The mass ratio of the talc powder to the fluorene cyclic amide is 1:6-8.

2. The nucleating agent for improving the wear resistance of PE materials according to claim 1, characterized in that: The fluorene ring amide is prepared by the following steps: (1) 6-methyl-2-pyridinecarboxylic acid is subjected to an acylation reaction to obtain a pyridine intermediate; (2) The pyridine intermediate is reacted with 2,7-diaminofluorene to obtain the fluorene cyclic amide.

3. The nucleating agent for improving the wear resistance of PE materials according to claim 2, characterized in that: The specific method of step (1) is as follows: add 6-methyl-2-pyridinecarboxylic acid, thionyl chloride and a dehydrating agent into a reactor, heat to 70-80° C., reflux for 24-36 hours, evaporate, wash and dry to obtain the pyridine intermediate.

4. The nucleating agent for improving the wear resistance of PE materials according to claim 3, characterized in that: The dehydrating agent is selected from one of dicyclohexylcarbodiimide, N,N'-diisopropylcarbodiimide or 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide; the mass ratio of 6-methyl-2-pyridinecarboxylic acid to thionyl chloride is 1:8-12.

5. The nucleating agent for improving the wear resistance of PE materials according to claim 2, characterized in that: The specific method of step (2) is: adding pyridine intermediate, 2,7-diaminofluorene, catalyst and organic solvent into a reactor, heating to 60-70°C for 6-8 hours, filtering, washing and drying to obtain the fluorene cyclic amide.

6. The nucleating agent for improving the wear resistance of PE materials according to claim 5, characterized in that: The catalyst is selected from one of triethylamine and triphenylphosphine; the organic solvent is selected from one of N,N-dimethylformamide, dichloromethane and tetrahydrofuran; the mass ratio of the pyridine intermediate to 2,7-diaminofluorene is 1:1.5-2.

7. The method for preparing the nucleating agent for improving the wear resistance of PE materials according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: adding talcum powder and fluorene cyclic amide in a proportion in a reactor, heating to 50-60° C. for dehydration and mixing for 30-40 minutes, and vacuum drying to obtain the nucleating agent for improving the wear resistance of PE materials.

8. Use of the nucleating agent for improving the wear resistance of PE materials according to any one of claims 1 to 6 in PE materials.

Citation Information

Patent Citations

  • Successively biaxial-oriented porous polypropylene film and method for producing the same

    JP2008111134A

  • Novel amide compounds

    KR100266916B1